Optimizing Sexual Education: Increasing Knowledge of Teenage Members of PIK-R SMAN 6 Padang - Dien Gusta Anggraini Nursal; Aisyah Addini Putri; Latifa Latifa; Silsabilillah Silsabilillah; Siska Windari (Warta Pengabdian Andalas, 2024)
Adolescents are at an age that is vulnerable to sexually deviant behavior. In this phase, providing sexual education is the right step to prevent deviant sexual behavior by teenagers. The number of deviant behaviors in adolescents can affect their reproductive health for the next life. This counseling aims to increase the knowledge of adolescents at SMAN 6 Padang regarding adolescent sexual behavior such as adolescent nutrition, adolescent psychology, adolescent growth and development, adolescent sexuality, reproductive tract infections (ISR) and STIs, HIV/AIDS prevention, and reproductive health for the future, which will come. The activity methods used are counseling and active class sharing using PowerPoint media, posters, and leaflets, as well as a questionnaire with a total of 30 questions; the targets of this activity are students who are members of PIK-R at SMAN 6 Padang. There was an increase in the average response knowledge during the pre-test of 66.75 and post-test of 84.00 with a pre-test standard deviation value of 16.802 and a post-test standard deviation value of 13.338. Based on statistical tests on the frequency distribution results, there was an increase in question scores; the results of the gain score test were low on HIV/AIDS material (0.230) and reproductive health of the elderly and reproductive age (0.257). The gain score results were moderate in child growth and development (0.634), sexuality, gender, and domestic violence (0.692), reproductive tract infections (0.375), reproductive health psychology (0.454), and adolescent nutrition (0.474). From these results, it was concluded that there was an average difference between the pre-test and post-test participants' knowledge, so it could be said that there was an influence of sexual behavior education outreach activities on adolescents. The hope is that after this activity, adolescents will care more and know how important education and education regarding sexuality is for adolescents and can avoid various kinds of sexually transmitted diseases, leading to a healthier and more informed generation in the future.